Integrated nutrient management with cow urine foliar application in wheat (Triticum aestivum) - SADHUKHAN, RAHUL; BOHRA, J S; SINGH, RAJIV KUMAR; HASANAIN, MOHAMMAD; SEN, SUMAN; MONDAL, BHABANI PRASAD (The Indian Journal of Agricultural Sciences, 2020)
The combination of inorganic fertilizers (100% RDF) with foliar application of 100% concentration of cow urine as organic source of nutrients enhanced growth and yield parameters of wheat. Hence, cow urine application with variable RDF levels could be an effective combination as integrated nutrient management tool for enhancing yields of field crops.